Subhaloes gone Notts: spin across subhaloes and finders - Onions, Julian; Ascasibar, Yago; Behroozi, Peter; Casado, Javier; Elahi, Pascal; Han, Jiaxin; Knebe, Alexander; Lux, Hanni; Merchán, Manuel E.; Muldrew, Stuart I.; Neyrinck, Mark; Old, Lyndsay; et al. (Monthly notices of the Royal Astronomical Society, 2013)
We present a study of a comparison of spin distributions of subhaloes found associated with a host halo. The subhaloes are found within two cosmological simulation families of Milky Way-like galaxies, namely the Aquarius and GHALO simulations. These two simulations use different gravity codes and cosmologies. We employ 10 different substructure finders, which span a wide range of methodologies from simple overdensity in configuration space to full 6D phase space analysis of particles. We subject the results to a common post-processing pipeline to analyse the results in a consistent manner, recovering the dimensionless spin parameter. We find that spin distribution is an excellent indicator of how well the removal of background particles (unbinding) has been carried out. We also find that the spin distribution decreases for substructures the nearer they are to the host haloes, and that the value of the spin parameter rises with enclosed mass towards the edge of the substructure. Finally, subhaloes are less rotationally supported than field haloes, with the peak of the spin distribution having a lower spin parameter.